Global justice, poverty and maternal mortality - Flor de María Cáceres M (Revista Facultad Nacional de Salud Pública, 2010)
Global justice is currently situated in an ambiance of tension and debate, facing a series of statements attempting to explain relationships among countries, based on the background of agreements already accomplished by supranational agencies. This network of relationships, not always fair nor equitable, has resulted in an increased accumulation of wealth in just a few hands and poverty in a growing number of people in poor countries and geographic areas with restrictions to access both to resources and to technological and scientific advances. Poverty, exclusion and inequalities limit all together the opportunities for development in these communities, with the outcome of serious consequences such as the deterioration in basic indicators of development. Maternal mortality rate (mm) is considered a sentinel indicator since it belongs in most cases to premature deaths which would be avoidable through proper measures in education, health promotion and timely access to quality health services. The purpose of this essay is to defend the thesis that the lack of global justice has limited the scope of the goals related to poverty and mm reduction